129 Network controllability and regional gene expression explain visual hallucinations in Parkinson's. Issue 6 (27th May 2022) - Zarkali, Angeliki; McColgan, Peter; Ryten, Mina; Reynolds, Regina; Leyland, Louise-Ann; Lees, Andrew J; Rees, Geraint; Weil, Rimona S
Abstract : Visual hallucinations are common in Parkinson's (PD) and associated with poorer prognosis. Imaging studies have shown white matter and functional changes in PD-hallucinations 1 2 but the biological factors underlying selective vulnerability of brain regions are unknown. We performed diffusion-weighted imaging in 100 PD patients (81 without hallucinations [PD-non-VH], 19 with hallucinations [PD-VH]) and 34 controls. We used network-based statistics to identify structural con- nectivity changes in PD-VH and performed an analysis of controllability, an emerging technique that allows quantification of influence across the rest of the network. We used the Allen brain atlas to identify regional gene expression patterns associated with affected areas of the network. We identified a subnetwork of reduced connectivity in PD-VH. Within this network, PD-VH showed reduced controllability (influence over other brain regions), than PD-non-VH (U=526, p=0.014) and controls (U=176.5, p=0.003). This subnetwork appears to be critical for brain integration, as even in controls, nodes with high controllability were more likely to be within the subnetwork (U=572.5, p<0.001). Gene expression analysis revealed downregulated genes related to mRNA metabolism and upregulated genes related to membrane localisation. Our findings provide insights into how hallucinations are generated, with breakdown of a key structural subnetwork that exerts control across distributed brain regions. Reference: Shine, et al . The role of dysfunctional attentional control networks in visual misperceptions in Parkinson's disease. HumBrainMapp;2014. a.zarkali@ucl.ac.uk